PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN EKONOMI MELALUI BADAN USAHA MILIK DESA (BUM DESA) NGASO MANDIRI DI DESA NGASO KECAMATAN UJUNGBATU KABUPATEN ROKAN HULU TAHUN 2016-2017 - Herlina, Siti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Refering to legislation governing the village, specifically law number 6 of 2014 concluded that village-owned enterprises are a village economic institution that has an important role in realizing the welfare of the village community. In government regulationn number 43 of 2014 states that the establishment of village-owned enterprises carried out tharough village meetings and determined by village regulation, therefor the Rokan Hulu district government forms a village-owned enterprises based on the rules of Rokan Hulu regent number 64 of 2014 about instruction for implementing village-owned enterprises. Community participation in economic deevelopment through village-owned enterprises discusses about how community involvement in the management of village-owned enterprises, also the factors the support the success of village-owned enterprises in running a business program in Ngaso village. While the purpose of this study is to find out community participation in economic development through village-owned enterprises and to find out the factors the influence the success of the village-owned enterprises. The result of this study are that community participation in village-owned enterprises Ngaso Mandiri in Ngaso village ot was quite high because many village community used the village-owned enterprises ti improve the economy and also the village community is active in saving money at the villlage-owned enterprises. But it is not in line with the activity of the user in terms of refunds so that the village-owned enterprises have a number of arrears.Keywords: Community Participation, Village-Owned Enterprises